The newsroom, Big Data and social media as information sources - Renó, Denis; Renó, Luciana (Estudios sobre el Mensaje Periodístico, 2015)
Since the emergence of the Internet, the further development of Web 2.0 and its narrative possibilities, journalism is no longer the same thanks to shared spaces (social media) and research of contents algorithms (Big Data). The article proposes, based on a bibliographic and documentary research, and empirical observation of the market and from the point of view of the participant, an understanding of the composition of contemporary newsrooms and production of transmedia content while intended to give a view data from social media. It is expected therefore to propose a reflection on the professional and cognitive relationship between journalists and professionals in the field of technology.